2021
DOI: 10.3389/fcell.2021.734897
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of S-Palmitoylation in Cancer Stem Cells of Lung Adenocarcinoma

Abstract: S-palmitoylation, catalyzed by a family of 23 zinc finger Asp-His-His-Cys (DHHC) domain-containing (ZDHHC) protein acyltransferases localized on the cell membrane. However, stemness genes modulated by ZDHHCs in lung adenocarcinoma (LUAD) remain to be defined. Previously, we have constructed a network of cancer stem cell genes, including INCENP, based on mRNA stemness indices (mRNAsi) of LUAD. INCENP has the function of a chromosomal passenger complex locating to centromeres, which is performed by the conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…It was found that ZDHHC5, ZDHHC17, ZDHHC18, and ZDHHC23 promote cellular self-renewal by targeting glioma stem cells, which in turn induces malignant progression of tumor cells. [26][27][28] We constructed a stable overexpression cell model and conducted functional experiments that identified inhibitory factors for tumor cell growth associated with a high expression of ZDHHC11B. We then conducted tumorigenic experiments in mice that confirmed these results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was found that ZDHHC5, ZDHHC17, ZDHHC18, and ZDHHC23 promote cellular self-renewal by targeting glioma stem cells, which in turn induces malignant progression of tumor cells. [26][27][28] We constructed a stable overexpression cell model and conducted functional experiments that identified inhibitory factors for tumor cell growth associated with a high expression of ZDHHC11B. We then conducted tumorigenic experiments in mice that confirmed these results.…”
Section: Discussionmentioning
confidence: 92%
“…Our study revealed that ZDHHC11B could be a protective factor for LUAD and its low expression was negatively correlated with the prognosis of patients with LUAD. It was found that ZDHHC5, ZDHHC17, ZDHHC18, and ZDHHC23 promote cellular self‐renewal by targeting glioma stem cells, which in turn induces malignant progression of tumor cells 26–28 . We constructed a stable overexpression cell model and conducted functional experiments that identified inhibitory factors for tumor cell growth associated with a high expression of ZDHHC11B.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the ZDHHC family in cancer has been widely reported. For example, ZDHHC5 has been found to regulate cancer stem cells and associated with malignant prognosis in lung adenocarcinoma (38), ZDHHC9 has been found to induce and stabilize PD-L1 protein, then drive cancer cells from immune surveillance in breast cancer (39), and the melanocortin-1 receptor palmitoylated by ZDHHC13 has been found to promote pigmentation and protect against melanoma (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of protein palmitoylation is catalyzed by the PAT family, which contains zinc finger structures (ZDHHCs). PAT and APT enzyme function is known to be associated with cancer, and the regulation of these enzymes has been suggested as a potential target for cancer treatment [ 162 , 163 , 164 ].…”
Section: Palmitoylationmentioning
confidence: 99%